Garlic Extracts Nanoliposome as an Enhancer of Bioavailability of ABA and Thiamine Content and as an Antifungal Agent Against Fusarium oxysporum f. sp. pisi Infecting Pisum sativum - Barbara Kutasy; Géza Hegedűs; Márta Kiniczky; József Péter Pallos; Ágnes Nagy; István Pócsi; Klaudia Pákozdi; Máté Kállai; Csaba Weingart; Katalin Andor; Bettina Kovács; Eszter Virág (Agronomy)
Fusarium infections in Pisum sativum L. crops present a major constraint to cultivation, leading to substantial yield losses. However, effective disease management strategies, particularly the implementation of biological control methods, offer promising approaches for mitigating infection severity and limiting pathogen spread. In P. sativum cultivation, pathogen control is particularly challenging due to the limited penetration of pesticides into the leaves. This is attributed to the dense crystalline plate structure within the leaf cuticle, which acts as a barrier, reducing the efficacy of conventional chemical treatments. Therefore, optimizing the formulation of biopesticides and plant conditioning agents is essential to improve the absorption and bioavailability of active ingredients, ensuring more effective disease management in P. sativum cultivation. This study examined the exogenous effects of garlic extracts in different formulations, including EliceVakcina (liposomal formulation), Garlic-lipo (liposomal formulation), and Garlic-oil (oil-based formulation), which contained high concentrations of abscisic acid (ABA) at 6.3, 81, and 80.4 µg g−1, respectively. Transcriptomic profiling, including the identification of Differentially expressed genes (DEGs) and KEGG pathway analysis of EliceVakcina-treated field samples, revealed a significant upregulation of stress- and defence-related genes, as well as pathways associated with thiamine metabolism and ABA signalling. Notably, key defence genes, including pathogenesis-related (PR1, PR2, PR4, PR5) and SnRK2, were overexpressed, indicating an enhanced stress response. HPLC-DAD analytical investigations confirmed the activation of the thiamine biosynthesis pathway, demonstrating a 14.3% increase in vitamin B1 content. Furthermore, the absence of Fusarium infection in the treated small-plot field cultures suggests that the tested garlic extracts formulation functions as a promising preventive biostimulant against plant fungal diseases.